2009
DOI: 10.1111/j.1365-3121.2009.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharaonic necrostratigraphy: a review of geological and archaeological studies in the Theban Necropolis, Luxor, West Bank, Egypt

Abstract: We present a review of archaeological and geological studies on the West Bank as a basis for discussing the geological setting of the tombs and geologically related problems with a view to providing archaeologists with a framework in which to conduct their investigations on the restoration, preservation and management of the antique monuments. Whereas the geology of the Upper Nile Valley appears to be deceptively simple, the lithological succession is vertically variable, and we have recognized and defined sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Ancient Egyptians constructed houses, palaces, temples and tombs mainly of environmental stones (Falana et al, 2020) and limestone and sandstone was the most commonly used materials in the construction of sacred buildings in Egypt because of its resistant to harsh weather. During the period of Queen Hatshepsut, Hatshepsut temple was built of local materials from Thebes limestone extracted from ancient quarry in Gebel Qurna (Aubry et al, 2009), (Pawlicki, 2017) (King, 2017). The study of Graue et al, (2007) revealed that severe deterioration results into the structural disintegration of rock masses, which is as a result of a clearly pronounced cataclastic overprint and has become a major structural problem since the tomb's origin.…”
Section: Introductionmentioning
confidence: 99%
“…Ancient Egyptians constructed houses, palaces, temples and tombs mainly of environmental stones (Falana et al, 2020) and limestone and sandstone was the most commonly used materials in the construction of sacred buildings in Egypt because of its resistant to harsh weather. During the period of Queen Hatshepsut, Hatshepsut temple was built of local materials from Thebes limestone extracted from ancient quarry in Gebel Qurna (Aubry et al, 2009), (Pawlicki, 2017) (King, 2017). The study of Graue et al, (2007) revealed that severe deterioration results into the structural disintegration of rock masses, which is as a result of a clearly pronounced cataclastic overprint and has become a major structural problem since the tomb's origin.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the hill above the KV62 tomb is constituted both by limestone of the Thebes formation and by natural aerated debris from the valley sides. Further details on the geology and on the properties of the materials could be found for example in Wust and McLane, 2000;Aubry et al, 2009, Dupuis at al., 2011, King et al, 2017 and other references cited therein. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…This study is an outcome of the field-mapping project of the Theban International Geological Project (TIGA; Aubry et al, 2009a), which has as its goal the construction of a geological map for the West Bank at Thebes. It is based on the careful analysis of geometrical relationships in a region of sharp contrasts where areas with well-exposed stratigraphies are juxtaposed with areas whose geological features are hidden below thick covers of screes, rubbles and breccias.…”
Section: Iii-methodologymentioning
confidence: 99%
“…The tombs of the Valley of the Queens were excavated at the base of a massive tilted block (Cobbold et al, 2008;Aubry et al, 2009a) that towers over the Wadi el-Melikat (Fig. 18a).…”
Section: Iv-4 Hills Of the Valley Of The Queensmentioning
confidence: 99%